Fibroblast Growth Factor Receptor-Mediated Rescue of x-Ephrin B1-Induced Cell Dissociation in Xenopus Embryos - Chong, Lisa D. (American Society for Microbiology, 2000)
The Eph family of receptor tyrosine kinases and their membrane-bound ligands, the ephrins, have been implicated in regulating cell adhesion and migration during development by mediating cell-to-cell signaling events. Genetic evidence suggests that ephrins may transduce signals and become tyrosine phosphorylated during embryogenesis. However, the induction and functional significance of ephrin phosphorylation is not yet clear. Here, we report that when we used ectopically expressed proteins, we found that an activated fibroblast growth factor (FGF) receptor associated with and induced the phosphorylation of ephrin B1 on tyrosine. Moreover, this phosphorylation reduced the ability of overexpressed ephrin B1 to reduce cell adhesion. In addition, we identified a region in the cytoplasmic tail of ephrin B1 that is critical for interaction with the FGF receptor; we also report FGF-induced phosphorylation of ephrins in a neural tissue. This is the first demonstration of communication between the FGF receptor family and the Eph ligand family and implicates cross talk between these two cell surface molecules in regulating cell adhesion.